Experimental study on the effect of argon shielding gas on the suppression of nitrogen arc anode ablation. (15th September 2022) - Hu, Ya-Hao; Meng, Xian; Huang, He-Ji; Shao, Ke; Murphy, Anthony B; Huang, Kai; Sun, Su-Rong; Wang, Hai-Xing
Abstract: The high heat flux density of the DC arc often leads to severe anode ablation, which is a key factor limiting the wider use of the DC plasma torches. In this study, a series of comparative experimental studies are conducted with the goal of suppressing nitrogen arc anode ablation by combining argon shielding flow and anode structure. It is found that for the planar electrode structure, the use of argon shielding gas can alleviate the ablation of the anode by nitrogen arc to some extent. If a boron nitride channel is installed on the anode surface to constrain the argon shielding flow, the electrode ablation can be significantly reduced. The experimental results show that there is no significant ablation on the anode surface after 1 h of operation of the nitrogen arc device with an arc current of 100 A. Further analysis reveals that, on the one hand, argon shielding gas can extend the range of motion of the nitrogen arc root along the anode surface and increase the speed of arc root motion, which has the effect of expanding the time-averaged arc anode attachment area. On the other hand, argon shielding gas can also increase the size of the nitrogen arc root and decrease the temperature of the arc root. The use of constraining channels can effectively control the range of motion of the arc root along the anode surface and strengthen the influence of argon shielding gas. The combination of these effects can substantially suppress the anode ablation of the DC arc device.